PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO BERBASIS MP3 DALAM MATERI DINAMIKA PENDUDUK BENUA-BENUA DI DUNIA KELAS IX SMP LABORATORIUM KOTA JAMBI - Susanti, Eli; Santika Andari, Ravia (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2024)
This research and development was raised from problems that arose in Jambi City Laboratory Junior High School, namely the lack of teachers using media, lack of facilities to support the learning process, and teachers only using textbooks as tools. This research has the purpose of how to develop and feasibility of mp3-based audio media. The development model used is ADDIE which includes five stages, namely Analysis, Design, Development, Implementation, and finally Evaluation. The developed media is then validated by media experts and material experts. In field trials, three stages of research were carried out, namely one to one trials getting a score of 76.84% in the "Enough" category, small group trials getting a score of 86.35% in the "Very Feasible" category, and field test trials getting a score of 83.68% in the "Very Feasible" category. Thus, it can be concluded that MP3-based Audio media is "feasible" to use for students.